Epidemiological factors and clinical profile of meconium aspiration syndrome in newborns admitted in rural tertiary centre - V. R., Gokul Ganesh; Mullainathan, Sucindar; Sivaprakasam, Chidambaranathan (International Journal of Contemporary Pediatrics, 2023)
Background: Meconium aspiration syndrome is a severe life-threatening illness in the neonate and is a major cause of perinatal morbidity and mortality. MSAF is reported around 10 to 20% of live births in which MAS seen around 5-10%. Various maternal and neonatal factors have been found associated with MAS which lead to several complications in the neonates and succumb to the disease. Methods: The present study is a observational study was done on 59 babies admitted in NICU of Government medical college, Chidambaram for a period of 1 year and 2 months who fulfilled the clinical criteria for diagnosing MAS. Babies born with MSAF were resuscitated as per NRP guidelines and observed for their immediate outcome. Results: Out of 460 MSAF babies, 59 developed MAS with incidence of (12.8%). MAS was common with thick meconium (55.9%) compared to thin with male preponderance (54.2%) and Primi gravida (74.6%). MAS occurred more in babies having fetal distress and antenatal risk factors like PIH, PROM, and anaemia. MAS was common in babies born through normal vaginal delivery and in term gestation of 37-40weeks with mean birth weight of 2860±394. 1minute APGAR score less than 7 in (57.6%) MAS babies and most common complications were PPHN, seizures and pneumothorax. Mortality in MAS was around (13.5%) with most common cause was hypoxic ischemic encephalopathy. Conclusion: Babies with MAS requires proper diagnosis and careful decisions are made about the timely intervention which reduces morbidity and mortality.